Kinetoplast Genome of Leishmania spp. Is under Strong Purifying Selection - Gerasimov, Evgeny S; Novozhilova, Tatiana S; Zimmer, Sara L; Yurchenko, Vyacheslav (Tropical medicine and infectious disease, 2023)
Instability is an intriguing characteristic of many protist genomes, and trypanosomatids are not an exception in this respect. Some regions of trypanosomatid genomes evolve fast. For instance, the trypanosomatid mitochondrial (kinetoplast) genome consists of fairly conserved maxicircle and minicircle molecules that can, nevertheless, possess high nucleotide substitution rates between closely related strains. Recent experiments have demonstrated that rapid laboratory evolution can result in the non-functionality of multiple genes of kinetoplast genomes due to the accumulation of mutations or loss of critical genomic components. An example of a loss of critical components is the reported loss of entire minicircle classes in Leishmania tarentolae during laboratory cultivation, which results in an inability to generate some correctly encoded genes. In the current work, we estimated the evolutionary rates of mitochondrial and nuclear genome regions of multiple natural Leishmania spp. We analyzed synonymous and non-synonymous substitutions and, rather unexpectedly, found that the coding regions of kinetoplast maxicircles are among the most variable regions of both genomes. In addition, we demonstrate that synonymous substitutions greatly predominate among maxicircle coding regions and that most maxicircle genes show signs of purifying selection. These results imply that maxicircles in natural Leishmania populations remain functional despite their high mutation rate.
Keywords: genome instability; SNP; leishmania donovani; L. turanica; L. major; L. infantum